Calculation of the creation and annihilation operators of a free particle in the light cone coordinate formalism - Jorge Kysnney Santos Kamassury; Damião Pedro Meira Filho; Charles da Rocha Silva; João Bosco Soares Pampolha Júnior; Robhyson Denys Rodrigues da Silva; Asael Ribeiro Pinto (The Journal of Engineering and Exact Sciences)
This work didactically presents the mathematical procedures required for the construction of the creation and annihilation operators for a free quantum particle considering the coordinates of the light cone. For that, the relationships between the aforementioned coordinates and the coordinates (ct, x, y, z) are listed, in addition to the use of the Klein-Gordon-Fock equation in the formalism of the light cone coordinates. Finally, the temporal evolution operator and the quantum operators of creation and annihilation of the integral type of motion are obtained.